Parental altruism, missing credit markets and growth - Michael Hatcher; Panayiotis M. Pourpourides (Cardiff University, Cardiff Business School, 2018)
Parental transfers towards the education of children are non-trivial, especially in countries, characterized by both imperfect credit markets and high economic growth rates. In this paper, we analyze the role of parental altruism on economic growth and dynamic efficiency, especially when credit markets for education loans are missing. We demonstrate conditions under which missing or imperfect credit markets increase economic growth and do not hinder dynamic efficiency. We also show that a newly constructed index of parental altruism, orthogonal to income effects, exhibits high cross-country correlations with model-implied measures of parental altruism at different levels of credit market development.
Keywords: I25; O16; O41; 330; Education; Human Capital; Credit Constraints; Growth